Server virtualization: success story in a Peruvian company - Yactayo Sánchez, Ángel David (2023)
The state company Sedapal contains a wide variety of obsolete technological standards that do not allow the growth of the technological infrastructure due to the limited financing by the state for the operation, maintenance, and renovation of a new structure. Due to this, the objective of this research is to design a server virtualization plan. Virtualization allows physical components to be abstracted and logically replicated. With this, a reduction in operation and maintenance costs can be achieved, in addition to allowing the new virtualized infrastructure to be scalable, expanding the resources that are acquired in the company. Likewise, the methodology used in this research is the waterfall methodology, which is divided into 5 stages, the first stage being the analysis of requirements, to move on to the design of the solution, its subsequent implementation, and the verification stage and ending with maintenance. The result obtained is the design prototype of a virtual architecture which allows a virtual technological infrastructure, concluding that the methodology and software used allow the design of a virtualization plan that can be applied to companies.